Influence of work-related psychosocial factors on the prevalence of chronic pain and quality of life in patients with chronic pain - Hironori Imano; Akihiko Kitamura; Hiroyasu Iso; Keiko Yamada; Ko Matsudaira (BMJ Open, 2016)
Objectives Working is a common cause of chronic pain for workers. However, most of them need to continue working despite the pain in order to make a living unless they get a sick leave or retirement. We hypothesised that the therapeutic effect of vocational rehabilitation may depend on psychosocial factors related to the workplace. To test this hypothesis, we examined the association of work-related psychosocial factors with the prevalence of chronic pain or health-related quality of life (HRQoL) among workers with chronic pain.Methods We examined 1764 workers aged 20–59 years in the pain-associated cross-sectional epidemiological survey in Japan. The outcomes were (1) chronic pain prevalence among all workers and (2) low Euro QoL (EQ-5D <0.76; mean value of the current study) prevalence among workers with chronic pain according to the degree of workplace social support and job satisfaction. Workplace social support and job satisfaction were measured using the Brief Job Stress Questionnaire. Multivariable-adjusted ORs were calculated using a logistic regression model including age, sex, smoking, exercise, sleep time, work hours, body mass index, personal consumption expenditure, intensity of pain and the presence of severe depressive symptoms.Results Chronic pain prevalence was higher among males reporting job dissatisfaction compared with those reporting job satisfaction. No difference was observed among women. Chronic pain prevalence did not differ between workers of either sex reporting poor workplace social support compared with those reporting sufficient support. Among workers with chronic pain, low HRQoL was more frequent in those reporting job dissatisfaction. Similarly, low HRQoL was more frequent in patients with chronic pain reporting poor social support from supervisors or co-workers compared with patients reporting sufficient support.Conclusions Work-related psychosocial factors are critical for HRQoL in patients with chronic pain.